Dropout in the treatment of erectile dysfunction with PDE5: A study on predictors and a qualitative analysis of reasons for discontinuation - Carvalheira, Ana Alexandra (2012)
Phosphodiesterase type 5 inhibitors (PDE5) are currently the first line treatment for erectile dysfunction (ED). However, previous research shows that PDE5 treatments have high discontinuation rates. Understanding the reasons for discontinuing PDE5 will be necessary to optimize the response to treatment. Aim. The main goals were: (i) to analyze discontinuation rate of PDE5; (ii) to identify the discontinuation predictors; and (iii) to study the reasons for discontinuation using a qualitative methodology. Main Outcome Measures. The PDE5 discontinuation rates, predictors, and reasons for discontinuation treatment. Methods. A total of 327 men with clinical diagnosis for ED who had been treated with PDE5 were successfully interviewed by telephone, after giving their informed consent by snail mail. Telephone interviews, concerning their ongoing treatment, were carried out using a standardized questionnaire form with quantitative and qualitative items. Participation rate was 71.8%. Results. Of the total sample, 160 men (48.9%) had discontinued PDE5 treatment. The discontinuation rate was higher among men with diabetes (73%) and in iatrogenic group (65%), and lower in venogenic etiology (38.7%).We differentiated three groups of men who discontinued treatment (i) during the first 3 months (55.1%); (ii) between 4 and 12 months (26.9%); and (iii) after a period of 12 months (18%). Qualitative analyses revealed diverse reasons for discontinuation: non-effectiveness of PDE5 (36.8%), psychological factors (e.g., anxiety, negative emotions, fears, concerns, dysfunctional beliefs) (17.5%), erection recovery (14.4%), and concerns about the cardiovascular safety of PDE5 (8.7%) were the most common. Older men and men whose partners were involved in the treatment, were less likely to discontinue treatment. Conclusion. Half the subjects discontinued medication. Mostly, there was a combination of factors that led to discontinuation: non-effectiveness and psychosocial factors appear to be the main reasons. Addressing those factors will allow following up with appropriate focus on relevant topics in order to improve compliance.